AKTIVITAS ANTIOKSIDAN, KARAKTERISTIK KIMIA, DAN SIFAT ORGANOLEPTIK SUSU KECAMBAH KEDELAI HITAM BERDASARKAN VARIASI WAKTU PERKECAMBAHAN - Saptya Fajar Pertiwi; Siti Aminah; Nurhidajah - (Universitas Muhammadiyah Semarang, 2013)
Utilization of black soybean (Glycinesoja) received less attention are not as popular of the color yellow soybeans because it less attractive. Black soybeans contain phenolic compounds that function as antioxidants compounds for the body. In the germination of different ages, different metabolic phases occur. The purpose of this study was to determine the effect of black soybean germination time on antioxidant activity, total phenols, vitamin C, protein content, and organoleptic properties of milk black soybean sprouts. The study design used a mono factor completely randomized design with 5 treatments (32, 40, 48, 56, and 64 hours) and 4 replications. The results showed age germination of the antioxidant activity, total phenols and vitamin C levels to be high : 28.24%, ppm 112.392, 139.103 mg% ​​respectively for germination at 64 hours, while the protein content is low ie 1, 82%. There are differences in the effect of germination time of black soybean for antioxidant activity, total phenols, vitamin C, protein content, color, and aroma of black soybean sprouts milk. Black soybean sprouts milk acceptable to the panelists in terms of color, aroma, and flavor with an average score of 3 (love).